Comparison of donor-site morbidity and satisfaction between anterolateral thigh and parascapular free flaps in the same patient - Fischer, Sebastian; Klinkenberg, Marek; Behr, Björn; Hirsch, Tobias; Kremer, Thomas; Hernekamp, Jochen-Frederick; Kolbenschlag, Jonas; Lehnhardt, Marcus; Kneser, Ulrich; Daigeler, Adrien (Journal of reconstructive microsurgery, 2013)
The purpose of this study was to compare donor-site morbidity after anterolateral thigh (ALT) and parascapular (PS) free flap harvest in the same patient. A total of 13 patients were included in this study. Because of initial flap loss, each patient received ALT as well as PS free flap transplantation. A total of 10 patients were available for follow-up. The average follow-up time was 44.5 months. Besides physical examination, range of motion and scar dimensions were assessed to objectify donor-site deficiencies. The subjective donor-site morbidity was assessed by the patients using a self-report questionnaire. In addition, patients were requested to state their donor-site preference. ALT donor site revealed more sensitivity deficiencies compared with the PS harvest site (8 vs. 4). The latter provoked less functional impairments (1 vs. 2). Scar dimensions were larger at PS harvest site (25.8 × 4.3 cm vs. 23.3 × 3.6 cm). Patients' satisfaction was in favor of the PS donor site (1.9 vs. 2.7). Among the 10 patients, 7 patients preferred the PS and 3 patients preferred the ALT donor site. Comparison of donor-site morbidities in the same patient reveals a valuable tool to diminish individual bias. Despite the low number of cases, we were able to demonstrate the superiority of PS compared with ALT donor sites. The Level of Evidence of the study is III